OCT guidance during stent implantation in primary PCI: A randomized multicenter study with nine months of optical coherence tomography follow-up - Kala, Petr; Cervinka, Pavel; Jakl, Martin; Kanovsky, Jan; Kupec, Andrej; Spacek, Radim; Kvasnak, Martin; Poloczek, Martin; Cervinkova, Michaela; Bezerra, Hiram; Valenta, Zdenek; Attizzani, Guilherme F; et al. (International journal of cardiology, 2018)
AIMS: To assess the possible merits of optical coherence tomography (OCT) guidance in primary percutaneous coronary intervention (pPCI). METHODS AND RESULTS: 201 patients with ST-elevation myocardial infarction (STEMI) were enrolled in this study. Patients were randomized either to pPCI alone (angio-guided group, n=96) or to pPCI with OCT guidance (OCT-guided group, n=105) and also either to biolimus A9 or to everolimus-eluting stent implantation. All patients were scheduled for nine months of follow-up angiography and OCT study. OCT guidance led to post-pPCI optimization in 29% of cases (59% malapposition and 41% dissections). No complications were found related to the OCT study. OCT analysis at nine months showed significantly less in-segment area of stenosis (6% [-11, 19] versus 18% [3, 33]; p=0.0002) in favor of the OCT-guided group. The rate major adverse cardiovascular events were comparable at nine months in both groups (3% in the OCT group versus 2% in the angio-guided group; p=0.87). CONCLUSIONS: This study demonstrates the safety of OCT guidance during pPCI. The use of OCT optimized stent deployment in 1/3 of patients in this clinical scenario and significantly reduced in-segment area of stenosis at nine months of follow-up. Whether such improvements in OCT endpoints will have a positive impact on late clinical outcomes, they demand both a larger and longer-term follow-up study.
Keywords: následné studie; Female; lidé středního věku; Percutaneous Coronary Intervention; optická koherentní tomografie; Follow-Up Studies; ST Elevation Myocardial Infarction; koronární angioplastika; mužské pohlaví; Tomography, Optical Coherence; Humans; stenty uvolňující léky; časové faktory; infarkt myokardu s elevacemi ST úseků; lidé; Middle Aged; Drug-Eluting Stents; peroperační monitorování; Time Factors; senioři; ženské pohlaví; Monitoring, Intraoperative; Aged; Male